9m+5+1+4m=

Simple and best practice solution for 9m+5+1+4m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m+5+1+4m= equation:


Simplifying
9m + 5 + 1 + 4m = 0

Reorder the terms:
5 + 1 + 9m + 4m = 0

Combine like terms: 5 + 1 = 6
6 + 9m + 4m = 0

Combine like terms: 9m + 4m = 13m
6 + 13m = 0

Solving
6 + 13m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 13m = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 13m = 0 + -6
13m = 0 + -6

Combine like terms: 0 + -6 = -6
13m = -6

Divide each side by '13'.
m = -0.4615384615

Simplifying
m = -0.4615384615

See similar equations:

| 7a+4=-14 | | 2(y+7)=32 | | 12y=8 | | =2*4x*3y-4x*7y | | 8y-9-3y+8=8 | | 5-(x-3)=-25 | | 3a-4=10-4a | | 3(-4)[2(-2)+4(3)(-3)+8(-4)]=x | | 44-66y+65y+5=9 | | 2x^2+19x-8.9=0 | | -2x=-11 | | -111=4x+7x+10 | | 36+2c=62 | | (8-10h)= | | 25x^4-20x^2y^2+4y^4=0 | | 0.1*x-y=16.1 | | g-82=93 | | 36+2c=72 | | (X+2)-(3x-3)=x+3 | | 7=(1+5n)+6(k+5) | | 2x+9-5(x+1)=4x+8 | | 65h=130-3h | | 50-19+5c=51 | | 8x^2+48x+8y^2+32y-96=0 | | 20x-5=6x+6 | | 3r^2+13r-110=0 | | 3(y-9)=10 | | 4(2x+10)=2(4x+20) | | 0.1*x-y=10.1 | | 20X-5X=8X+21 | | 140-5x=3x+20 | | 26=i-14 |

Equations solver categories